STRATEGI PEMASARAN TAHU KHAS DADAPAN DI DESA PEJENG KECAMATAN TAMPAKSIRING - I Made Jigra Wedanta; Ni Gst. Ag.Gde.Eka Martiningsih; I Made Tamba (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
The title of this study is a Marketing Strategy of Dadapan Tofu In Pejeng Village, Subdistrict of Tampaksiring. This study aims to identify and analyze internal factors that become the strengths and weaknesses of tofu typical of dadapan in Pejeng village. The strength factor is the pricing of tofu in accordance with the quality to achieve customer satisfaction, the location of strategic dadapan tofu companies, and service from the industry to consumers tofu dadapan. Weakness factors are strategies used not yet maximized, limited promotions, and limited business capital. The opportunity factor is the development of management technology, able to compete with other companies, continuous raw materials are guaranteed. Threat factors are environmental competition, fluctuations in prices and raw materials, competition for quality and quantity of tofu between tofu industries. Marketing strategies know typical of dadapan is in quadrant I, meaning that strategies that can be implemented in quadrant I is growing and building. Startegi alternative that needs to be improved more intensively is strategy SO (Strength Opportunities) Make use of the holiday season, cultural events, and various visits in government agencies by working between industries to meet market demand. The government provides assistance in the procurement of facilities in the sales industry typical of dadapan tofu that is easy to reach consumers, especially in Pejeng Village, Gianyar Regency.